1999
DOI: 10.1016/s1010-7940(99)00052-4
|View full text |Cite
|
Sign up to set email alerts
|

Thymectomy for myasthenia gravis: a 27-year experience1

Abstract: Thymectomy is effective in the management of patients with MG at all stages with low morbidity. Patients with thymoma present a less favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
3
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 18 publications
7
57
3
3
Order By: Relevance
“…Ozdemir et al (18) found a 7-fold increased risk of clinical worsening in patients with stage IIb and III disease. Nieto et al (8) found that patients with stage I and III disease had a better outcome than those with other stages.…”
Section: Resultsmentioning
confidence: 99%
“…Ozdemir et al (18) found a 7-fold increased risk of clinical worsening in patients with stage IIb and III disease. Nieto et al (8) found that patients with stage I and III disease had a better outcome than those with other stages.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that remission rate (RR), raised in: patients operated shortly after diagnosis, generalized mild-to-moderate MG, and involuted thymus (24). Venuta et al in their 27-year experience review reported a 25% CSR at the 10-year follow-up (23).…”
Section: Patient and Tumor Characteristicsmentioning
confidence: 99%
“…In the same year, Minniti et al [5] described two other cases of neoplastic masses in the middle mediastinum, only one of which was a thymoma and the other was a thymic cyst. The great experience of Venuta et al [6] correlated the results of thymectomy in the treatment of myasthenia gravis, concluding that patients suffering from thymomas present an unfavorable prognostic. Everything seems to indicate, from the 232 thymectomies performed by these authors 62 thymomas were located in the upper anterior mediastinum, if not this rare fact would have been mentioned.…”
Section: Fig 2 -Pre-operative Computer Tomography (A) and Chest Radimentioning
confidence: 99%
“…Revision of publications made by Minniti et al [5] did not find reports of thymomas in the middle mediastinum; these authors described a case of thymoma and one of a thymic cyst in the same region. Venuta et al [6] emphasized the value of thymectomy in the treatment of myasthenia gravis, as thymomas in 28.4% of the cases negatively influence the prognosis of treatment.…”
Section: Introductionmentioning
confidence: 99%